A preliminary study of 5-day mean flow patterns in relation to 5-day precipitation in north India during winter season (MAUSAM, 1960)
5-day mean charts of surface pressures and 700.mb contours have been prepared for the winter months of the years 1956 and 1957 and studied in relation to the precipitation distribution. The typical mean patterns which were mainly associated with rainfall m north India during the above period, are illustrated and discussed in some detail pressure and contour anomaly charts have also been prepared and examined with reference to the precipitation distribution. The speeds and tracks of the mean lows which moved eastwards affecting the weather over northern pats of the country have also been studied and the results incorporated in the paper.